2019
DOI: 10.25110/arqvet.v22i3.2019.7890
|View full text |Cite
|
Sign up to set email alerts
|

CASTRAÇÃO QUÍMICA EM SUÍNOS COM ÓLEO ESSENCIAL DE CRAVO DA ÍNDIA (Eugenia caryophyllata)

Abstract: Os suínos são a segunda proteína animal mais consumido do mundo, sendo que o Brasil é o quarto produtor mundial deste tipo de carne. Atualmente, por exigência do mercado consumidor externo e interno há uma grande demanda por produção de carne por meios orgânicos ecologicamente sustentáveis e que sigam a premissa de bem-estar animal. A castração é realizada em suínos machos para tornar a carne palatável e aceita pelos consumidores. A técnica tradicionalmente empregada é a cirúrgica, mas da maneira que é pratica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This standard mainly requires analgesia and anesthesia for surgical castration in pigs of any age (BRASIL, 2020). As a result, several studies seek new alternatives for producers using chemical castration as an option, a technique considered less invasive, more innovative and that reduces possible infections (LOPES; SILVA, 2014;SOTO, 2015), in addition to being considered an easy-to-perform technique in pigs (SILVA et al, 2019), as observed in the present study.…”
Section: Discussionmentioning
confidence: 58%
“…This standard mainly requires analgesia and anesthesia for surgical castration in pigs of any age (BRASIL, 2020). As a result, several studies seek new alternatives for producers using chemical castration as an option, a technique considered less invasive, more innovative and that reduces possible infections (LOPES; SILVA, 2014;SOTO, 2015), in addition to being considered an easy-to-perform technique in pigs (SILVA et al, 2019), as observed in the present study.…”
Section: Discussionmentioning
confidence: 58%